Correction: Understanding the reactivity of bis(propargyl) aromatic esters towards GAP: a theoretical exploration. (24th July 2017) - Sonawane, Sanjeevani H.; Banerjee, Shaibal; Sider, Arun K.; Talawar, Mahadev B.; Khan, Md Abdul Shafeeuulla
Abstract : Correction for 'Understanding the reactivity of bis(propargyl) aromatic esters towards GAP: a theoretical exploration' by Sanjeevani H. Sonawane et al., New J. Chem., 2017, DOI: 10.1039/c7nj01172e.